Tanggung Jawab Hukum Akuntan Publik atas Opini Laporan Audit terhadap Laporan Keuangan Menurut UU Nomor 5 Tahun 2011 tentang Akuntan Publik - Simanjuntak, Theodorus Agustinus; Ardiansyah, Ardiansyah (Neolectura, 2025)
A Public Accountant is a professional individual who has obtained permission from the Minister of Finance to provide services concerning Public Accountants under Law Number 5 of 2011. One of them is audit services for financial statement information. In making company policy decisions, both internal and external stakeholders rely heavily on information derived from audited financial reports. Financial report audits are essential for ensuring the accuracy and validity of information, supporting informed decision-making. Public accountants evaluate and provide independent opinions on the fairness of financial reports, based on by professional ethics and the Code of Ethics, free from external influences. An audit opinion must be based on evidence that meets current rules and regulations. Public Accountants are legally accountable for their opinions, adhering to audit standards, and disclosing relevant information. By following professional ethics, they ensure audit integrity and reduce fraud risk in financial statements, fostering stakeholder transparency and trust. Based on the explanation provided, this study is to understand the legal responsibility of Public Accountants for the financial report opinions that have been issued. This study will focus on two key issues: the responsibilities defined by UU No. 5 of 2011 for Public Accountants and the authorized parties involved in cases of violations by these accountants. Using normative legal methods and referencing laws such as UU No. 5 of 2011 on Public Accountants and international audit standards (ISA), it can be concluded that Public Accountants have legal responsibilities in issuing audit opinions on financial statements, which may lead to administrative sanctions.